Assessing the role of vertical leaves within the photosynthetic function of Styrax camporum under drought conditions - Feistler, A. M. [UNESP]; Habermann, Gustavo [UNESP] (Springer, 2012)
Previous evidence has demonstrated that vertical leaves of Styrax camporum, a woody shrub from the Brazilian savanna, have a higher net photosynthetic rate (P (N)) compared with horizontal leaves, and that it is detected only if gas exchange is measured with light interception by both leaf surfaces. In the present study, leaf temperature (T (leaf)), gas exchange and chlorophyll (Chl) a fluorescence with light interception on adaxial and also on abaxial surfaces of vertical and horizontal mature fully-expanded leaves subjected to water deficit (WD) were measured. Similar gas-exchange and fluorescence values were found when the leaves were measured with light interception on the respective surfaces of horizontal and vertical leaves. WD reduced P (N) values measured with light interception on leaf surfaces of both leaf types, but the effective quantum yield of PSII (I broken vertical bar(PSII)) and the apparent electron transport rate (ETR) were reduced only when the leaves were measured with light interception on the adaxial surface. WD did not decrease the maximum quantum yield of PSII (F-v/F-m) or increase T (leaf), even at the peak of WD stress. Vertical leaf orientation in S. camporum is not related to leaf heat avoidance. In addition, the similar P (N) values and the lack of higher values of I broken vertical bar(PSII) and ETR in vertical compared with horizontal leaves measured with light interception by each of the leaf surfaces suggests that the vertical leaf position is not related to photoprotection in this species, even when subjected to drought conditions. The exclusion of this photoprotective role could raise the alternative hypothesis that diverse leaf angles sustain whole plant light interception efficiency increased in this species.
Keywords: Brazilian savanna; chlorophyll fluorescence; gas exchange; leaf surface; paraheliotropism; Styracaceae